Mídias sociais, cultura pop e divulgação científica: um estudo do canal Nerdologia - Oliveira, Felipe Adriano Alves de (2021)
It is highlighted some of the main aspects of scientific dissemination, the act of communicating science to the public, being the social media, one of the vehicles part of this communication, such as the YouTube platform. In this sense, it proposes to analyze the Nerdologia channel as an integral part of this platform, being a channel focused on entertainment and dissemination of scientific knowledge through elements of pop culture. The study sought to identify the models of public communication of science in order to investigate the methods that the channel uses to communicate science with the public, its strategies, its main elements, and tools of disclosure, which had as sampling reference, the selection of the 50 most accessed videos between the years 2013 to 2019, in addition to contextualizing the public communication of science and the discussion involving the field of Science, Technology and Society, being the study area in which the present research focuses. The methodology used was Content Analysis that assisted in the processes of treatment and analysis of the data and information. The results obtained revealed the science communication models that focus respectively on the "Koru" model of Longnecker, also linked to informal education, and the "contextual" model of Lewenstein, in addition to the style of scientific dissemination, being classified as "independent". The research also addressed the issue of the aesthetic and sound elements of the channel and its discursivities. It was concluded that the Nerdologia channel seeks to disseminate and teach science in an implicit and independent way, using visual and sound resources as strategies to obtain greater views in their videos, always aiming at the context of their audience, as consumers of products of the Cultural Industry as part of Pop Culture.